Juridical Analysis of Criminal Acts in Environmental Pollution in Accordance to the 32 Law of 2009 Concerning Protection and Management Environment - Chaidir, Noor; Muhibbin, Moh.; Arief, Hanafi (Scholar Center, 2024)
This study aims to describe the regulation of criminal acts of environmental pollution in Indonesian positive law and to analyze the responsibility for criminal acts of environmental pollution according to Law Number 32 of 2009. This study uses normative legal research in the form of library research using three types of legal materials, namely primary, secondary and tertiary legal materials, qualitative descriptive research, normative juridical research, statutory and conceptual approaches. The results of the study stated that the regulation of criminal acts of environmental pollution in Indonesian positive law is regulated in Law Number 32 of 2009 concerning the Environment. This law stipulates that if environmental pollution and damage has already occurred, it is necessary to take repressive measures in the form of effective, consistent and consistent law enforcement against environmental pollution and damage that has occurred so as to apply the principle of primum remedium criminal law. The crime of environmental pollution is not only imposed on individual perpetrators of environmental crimes, but also on corporations. In addition, also to customary law communities based on the Constitutional Court decision No. 35/PUU-X/2012 by using conditionality in recognizing the existence of indigenous peoples as legal subjects which are still maintained as long as in reality they still exist and their existence is recognized, and confirmation of their existence is stipulated by Regional Regulations.